2017
DOI: 10.1101/gr.226068.117
|View full text |Cite|
|
Sign up to set email alerts
|

Deep experimental profiling of microRNA diversity, deployment, and evolution across the Drosophila genus

Abstract: To assess miRNA evolution across the genus, we analyzed several billion small RNA reads across 12 fruit fly species. These data permit comprehensive curation of species- and clade-specific variation in miRNA identity, abundance, and processing. Among well-conserved miRNAs, we observed unexpected cases of clade-specific variation in 5' end precision, occasional antisense loci, and putatively noncanonical loci. We also used strict criteria to identify a large set (649) of novel, evolutionarily restricted miRNAs.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 49 publications
1
43
0
2
Order By: Relevance
“…In addition, sex-chromosome drive is widespread in the obscura group: X-chromosome drive was first described in D. obscura, and has also been reported in pseudoobscura, persimilis, affinis, azteca, subobscura and athabasca [54] and is mediated through a testisspecific function (Y-bearing sperm have reduced function). Finally, a testis-specific class of hairpin (endo) siRNAs is required for male fertility in D. melanogaster [56], testes-restricted clustered miRNAs show rapid evolutionary turnover and are represented in large numbers in D. pseudoobscura [57], and suppression of sex-specific duplicates of S-Lap1 via a small-RNA mechanism has recently been implicated in the meiotic drive mechanism of D. pseudoobscura [58]. In this context, it is also interesting to note that Ago2 is involved in directing heterochromatin formation in Drosophila dosage compensation [10][11][12], and that in D.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, sex-chromosome drive is widespread in the obscura group: X-chromosome drive was first described in D. obscura, and has also been reported in pseudoobscura, persimilis, affinis, azteca, subobscura and athabasca [54] and is mediated through a testisspecific function (Y-bearing sperm have reduced function). Finally, a testis-specific class of hairpin (endo) siRNAs is required for male fertility in D. melanogaster [56], testes-restricted clustered miRNAs show rapid evolutionary turnover and are represented in large numbers in D. pseudoobscura [57], and suppression of sex-specific duplicates of S-Lap1 via a small-RNA mechanism has recently been implicated in the meiotic drive mechanism of D. pseudoobscura [58]. In this context, it is also interesting to note that Ago2 is involved in directing heterochromatin formation in Drosophila dosage compensation [10][11][12], and that in D.…”
Section: Discussionmentioning
confidence: 99%
“…A conservation analysis was first conducted to identify all miRNAs in the D. melanogaster genome. All mature miRNAs from the 12 Drosophila subspecies {Kozomara, 2014 #28} were mapped on the D. melanogaster genome and the miRNA loci then determined using criteria based upon the identification of miRNA hairpin-like secondary structures (specifically: adjusted minimal folding free energy (aMFE) < −20 and no branching adjacent to the miRNA/miRNA* duplex) a similar approach as in {Mohammed, 2018 #4633}. We then determined all 7 and 8nt seed regions for all mature miRNAs.…”
Section: Methodsmentioning
confidence: 99%
“…Micro RNAs (miRNAs), another group of non-coding RNAs, have been shown to directly modulate histone modifications and thus the chromatin accessibility to allow transcription of target genes [60]. Since miRNAs are highly tissue specifically expressed [61][62][63], these molecules provide an excellent mechanism to facilitate tissue specific chromatin accessibility.…”
Section: Pre-transcriptional Regulation -Chromatin States and Methylamentioning
confidence: 99%
“…Comparative studies in five mammals [136] and twelve Drosophila species [62] revealed that also non-coding RNA molecules evolve in a highly context dependent manner. For instance, high turnover rates have been associated with the underlying molecular mechanisms involved in miRNA maturation [62].…”
Section: Evolution Of Gene Expression Is Context Dependentmentioning
confidence: 99%